Afferent innervation of the kidney: projections to and processing in the central nervous system - Dailey-Krempel, Brianna; Evans, Louise C.; Osborn, John W.; Vulchanova, Lucy (Frontiers in Physiology, 2026)
FDA approval for catheter-based renal nerve ablation has sparked renewed interest in the role of renal nerves in hypertension and their potential contribution to other pathophysiologies. While the anti-hypertensive effects of catheter-based renal nerve ablation were thought to be due to the ablation of the sympathetic efferent nerves going to the kidney, preclinical hypertensive rodent studies and unexpected beneficial clinical outcomes have highlighted the renal afferent (sensory) nerves as a contributor to the pathogenesis of hypertension. Renal afferents are most abundant in the renal pelvis but also innervate the renal cortex. Their neurochemical and functional diversity remains to be fully elucidated. Tracing studies from the kidney to the central nervous system (CNS) have identified direct projections of spinal afferents with cell bodies in dorsal root ganglia to both the spinal cord and caudal brainstem. Few studies have suggested vagal innervation of the kidney with cell bodies in the nodose ganglia. The central processing of renal afferent input in brain autonomic circuits is not thoroughly understood. Regions involved in renal afferent input processing include the paraventricular nucleus of the hypothalamus and nucleus of the solitary tract which integrate peripheral sensory inputs with central homeostatic sensing regions including circumventricular organs. This review aims to summarize our current understanding of renal afferent anatomy including tracing and immunolabeling studies from the kidney to the CNS, the general mechanosensitive and chemosensitive subtypes in the kidney, and broadly discuss a potential pathway for the central processing of renal afferent input through autonomic and other homeostatic nuclei.